Pemanfaatan Sistem Peringatan Dini Erupsi Gunung Merapi sebagai Upaya Pengurangan Risiko Bencana Guna Mendukung Keamanan Nasional - Islami, Hafizh Surya; Widana, I Dewa Ketut Kerta; Subiyanto, Adi (Jagratara: Journal of Disaster Research, 2023)
Indonesia is recorded as having 129 volcanoes with active status and 500 volcanoes with inactive status, and 60% of Indonesia's active volcanoes have the potential to cause quite large eruptions. In recent years, volcanic activity from several volcanoes in Indonesia has begun to increase. It was recorded that 260 people died as a result of the eruption of Mount Merapi in KRB III. Volcanic eruption events can be predicted using an early warning system. A complete and effective early warning system consists of four interrelated elements. These four elements can be used as a reference in increasing the capacity of communities in disaster-prone areas of Mount Merapi. This research aims to analyze the early warning system for Mount Merapi activity as an effort to reduce disaster risk and utilize the early warning system for disaster risk reduction to support national security. The research uses qualitative methods with exploratory research. Based on the research results, the use of the early warning system for the eruption of Mount Merapi has four main elements to serve as a guide in dealing with the Mount Merapi eruption disaster, both in the form of elements of knowledge of the risk of the Mount Merapi eruption disaster, utilization and warning services, dissemination and communication, as well as readiness and ability to cope. So it can be concluded that the early warning system in Sleman Regency has fulfilled the aspects of dealing with the Mount Merapi eruption disaster.